Sustainability of chemical substitutes from agricultural and industrial by‐products - Phang, Lai‐Yee; Abd‐Aziz, Suraini; Gozan, Misri; Ibrahim, Mohamad F. (Wiley, 2023)
Sustainable production of chemical substitutes from agricultural and industrial by-products is the way to preserve resources and protect the environment. Hence, significant attention is directed toward developing green technologies to valorize these by-products. This increase in value can make the economics of chemical substitute production from by-products more feasible and workable. However, the cost of synthesizing chemical substitutes and productivity barriers is still very challenging. This chapter provides the policies and initiatives for the sustainable development of selected countries, as well as case studies on assessing the sustainability of selected chemical substitute production strategies, considering three perspectives includes environmental, economic, and social. This chapter presents two case studies on cellulase and biofertilizer production. The case studies discuss the cost and pinch analysis using the process simulation software Aspen Plus. The challenges and market opportunities will be covered.